2016
DOI: 10.1525/abt.2016.78.8.651
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Active Learning on Student Outcomes in Large-Lecture Biology Courses

Abstract: Learning theorists have provided ample evidence supporting the use of active, student-centered, social learning environments. However, little action has been taken within U.S. university curricula to transform lecture courses so that they include such teaching methods. By adding cooperative and collaborative activities into large-lecture, introductory biology courses, I was able to measure the impacts of such active-learning strategies on student attendance and performance. I gathered data from two investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…They are considered to be fundamental to the students' broader understanding of the discipline (Druger 2006), the important initial contact for prospective students to major or minor in the discipline, and for some the only venue for gaining scientific literacy (Labov 2004). Various studies have evaluated introductory undergraduate science courses by assessing teaching methods, curriculum, student performances, and student experiences (Wuellner 2015;Daniel 2016;Tasch and Tasch 2016). For example, Macdonald et al (2005) conducted a >2000-participant study on teaching methods in geoscience that surveyed instructors from academic units in the United States including earth science, environmental science, and hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered to be fundamental to the students' broader understanding of the discipline (Druger 2006), the important initial contact for prospective students to major or minor in the discipline, and for some the only venue for gaining scientific literacy (Labov 2004). Various studies have evaluated introductory undergraduate science courses by assessing teaching methods, curriculum, student performances, and student experiences (Wuellner 2015;Daniel 2016;Tasch and Tasch 2016). For example, Macdonald et al (2005) conducted a >2000-participant study on teaching methods in geoscience that surveyed instructors from academic units in the United States including earth science, environmental science, and hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, empirical research by Braxton, et al [59] demonstrated that learning strategies were not only related to social integration in HEIs but also helped build students' institutional and goal commitments and LOs. Similarly, Daniel [60] concluded that students who engaged in course collaborative activities and active-learning strategies showed significantly higher LO gains than those who did not.…”
Section: The Direct and Indirect Relationships Of Learning Strategies With Institutional And Goal Commitments Llls And Losmentioning
confidence: 99%
“…Active learning practices are known to support student learning (Michael 2006, Daniel 2016. Hands-on learning in the anatomy and physiology lab without the use of cadavers poses challenges.…”
Section: The New Model/revisionmentioning
confidence: 99%